Раскопки некрополей Илурата и Китея в 2008 г. - Хршановский, В.А. (Археологічні дослідження в Україні, 2009)
The paper is devoted to the research of the necropoleis of Bosporan cities Ilurat and Cytae. The structural peculiarities of the burials discovered during the excavations and the analysis of archaeological material obtained are considered here.